The new School Admission System (SAS) in Chile: contributions to equal opportunities in a context of school choice (Encuentros, 2022)
The School Admission System (SAS) is a centralized mechanism for assigning students among schools that receive fiscal resources. The objective of this article is to analyze the demand flows and the level of adjustment that SAS assignments have with parental educational preferences. Methodology: the article has a descriptive analysis approach and uses data from the 2018 school admission process. School choices are characterized according to demand profiles and the attributes of the educational offer. Results: The SAS has acceptable levels of effectiveness in the distribution of applicants, with low rejection rates and a high degree of compliance with the first preferences. Conclusions: the SAS is an efficient mechanism that equalizes opportunities in the allocation of vacancies, once reserved by arbitrary school selection, ensuring enrollment within a reasonable set of preferences, and therefore does not conflict with the principle of free parental choice.